ANALISIS KOMPARATIF PENENTUAN HARGA POKOK PRODUKSI DENGAN METODE HARGA POKOK PROSES (PROCESS COSTING) - Sriwedari, Tuti; Siregar, Waidan Nur; Pangaribuan, Hawila Sabta; Zahira, Tira Al (Program Studi Akuntansi Universitas Flores, 2026)
This study aims to examine and compare the application of the process costing method in determining the cost of goods manufactured (COGM) across various industrial sectors, including food and beverages, textiles, construction materials, agribusiness, and household industries. Using a descriptive-comparative literature review approach, the research analyzed ten scientific journals published between 2020 and 2025. The findings reveal that the implementation of process costing consistently enhances the accuracy of production cost calculations compared to traditional methods, as it accounts for all cost components proportionally at each stage of the process. Variations among industries are influenced by sector characteristics, the proportion of overhead costs, and the quality of cost recording systems. Therefore, process costing is proven to be effective in improving cost transparency, operational efficiency, and managerial decision-making accuracy.